The oxygen-deficiency-dependent Seebeck coefficient and electrical properties of mesoporous La0.7Sr0.3MnO3−x films. Issue 12 (29th February 2016) - Park, Chang-Sun; Lee, Hong-Sub; Shim, Dong Il; Cho, Hyung Hee; Park, Hyung-Ho; Kwon, Kwang-Ho
Abstract : The power factor of mesoporous LSMO films was enhanced with an increase in the surface area. Abstract : The thermoelectric power factor of La0.7 Sr0.3 MnO3 (LSMO) is closely related to its oxygen-deficient nature. In this study, the oxygen content of mesoporous LSMO films was controlled using various annealing atmospheres (oxygen, nitrogen, air, and argon) to investigate the relationship between oxygen deficiency and the power factor. The effect of the mesoporous structure on the power factor of the prepared LSMO films was also studied through analyses of structural and electrical properties. The oxygen-deficient state induces an increase in the lattice parameter of LSMO, which results in an increase in the electrical resistivity and an enhanced Seebeck coefficient. This phenomenon was emphasized upon the introduction of a pore structure in LSMO because of an increase of the unstable surface area. The oxygen-deficient state results in an increase in the amount of manganese in the Mn 3+ valence state and in an increase of the lattice parameter; these effects were confirmed through photoemission spectroscopic analysis. As a result, LSMO can be applied as a thermoelectric material because of the successful preparation of LSMO films with a mesoporous structure and because of the enhancement of the power factor as a consequence of increased oxygen deficiency.